2019
DOI: 10.1093/geront/gnz003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Trial Evaluation of a Peer Volunteering Active Aging Intervention: ACE (Active, Connected, Engaged)

Abstract: Background ACE (Active, Connected, Engaged) is a theory-informed, pragmatic intervention using peer volunteering support to promote active ageing in socially disengaged, inactive older adults. This study aimed to establish ACE’s feasibility and acceptability. Methods Fifty-four older adults were recruited as either peer volunteers (activators; n = 15) or participants (ACEs; n = 39). Participants were randomized to one-to-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(79 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…The Active, Connected, Engaged [ACE] study was a theory-informed, feasibility study which tested the use of peer volunteering support to promote active ageing in socially disengaged, physically inactive older adults [16,29]. In summary, 54 older adults were recruited into the ACE study as either peer volunteers (Activators; n=15) or participants (ACEs; n=39).…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The Active, Connected, Engaged [ACE] study was a theory-informed, feasibility study which tested the use of peer volunteering support to promote active ageing in socially disengaged, physically inactive older adults [16,29]. In summary, 54 older adults were recruited into the ACE study as either peer volunteers (Activators; n=15) or participants (ACEs; n=39).…”
Section: Designmentioning
confidence: 99%
“…The University of Bath (EP 11/12 98) and the University of Birmingham (ERN_18-0877) Research Ethics Committees ethically approved the study. See detailed information on recruitment in [16,29].…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the sample was relatively fit and lacked older individuals with mild and moderate limitations [ 10 ]. Another pilot study showed that a combination of initial motivation by a peer volunteer and subsequent activity such as walking in groups, yoga or dancing led to behavioural changes in older people and improved physical activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%